2018
DOI: 10.1166/jbn.2018.2629
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Polarization in Response to Varying Pore Sizes of 3D Polyurethane Scaffolds

Abstract: Activated macrophages dominate the progression of foreign-body response (FBR) and may be in a bimodal state, which determines the fate of biomaterials postimplantation. The purpose of this study was to investigate the phenotypic profile of macrophages polarized by waterborne biodegradable polyurethane (WBPU) scaffolds with different pore diameters (PU8, PU12, and PU16) both in vitro and in vivo. The results demonstrated that WBPU scaffolds with smaller pore sizes promoted the polarization of RAW 264.7 cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
1
8
2
Order By: Relevance
“…4 D). These results indicated that the grafts with medium and large pore sizes possessed more constructive tissue remodeling outcomes, and are consistent with the findings of previous studies that have also found larger pores induce a higher ratio of M2 to M1 macrophages in other materials [ 11 , 12 , 44 ]. All the results obtained from the rat carotid interposition model demonstrated that though the three different types of grafts had high patency rates and the potential for vascular remodeling, the grafts with medium and large pore sizes achieved higher patency rates and more constructive tissue remodeling outcomes than the grafts with small pores at 1 week and 4 weeks.…”
Section: Resultssupporting
confidence: 92%
“…4 D). These results indicated that the grafts with medium and large pore sizes possessed more constructive tissue remodeling outcomes, and are consistent with the findings of previous studies that have also found larger pores induce a higher ratio of M2 to M1 macrophages in other materials [ 11 , 12 , 44 ]. All the results obtained from the rat carotid interposition model demonstrated that though the three different types of grafts had high patency rates and the potential for vascular remodeling, the grafts with medium and large pore sizes achieved higher patency rates and more constructive tissue remodeling outcomes than the grafts with small pores at 1 week and 4 weeks.…”
Section: Resultssupporting
confidence: 92%
“…It has to be noted though that the difference in material, stiffness, and cell type must be kept in mind when making such comparisons. In addition, there is some inconsistency in literature regarding the effect of pore sizes on macrophages as it has been shown in other studies that larger pore sizes induce a more polarized morphology of macrophages while smaller ones confine them to a round shape ( Liang et al, 2018 ; Jiang et al, 2019 ). In light of this, further studies focusing on the effect of a softer scaffold with a similar geometry on the phenotype of microglia would be needed.…”
Section: Resultsmentioning
confidence: 99%
“…When used as the scaffold for tissue engineering, these tubular pores (as indicated by the yellow arrows) are beneficial to guide cell growth and extra cellular matrix deposition along the direction of the elongated pores arranged parallel to the surface/subchondral bone 1,28 . A large number of small pores (as indicated by the white arrows) with a diameter of approximately 10 μm are located at the pore wall surface, that is, the bimodal porous structures are interconnected, allowing for cell and nutrient transport throughout the scaffold 29,30 .
Figure 9The bimodal cellular structure (the white arrows represent small pores for nutrient transport, and the yellow arrows represent tubular pores for cell growth) and the cell size distribution of the WPVA/PEG-6000 (90/10) scaffold.
…”
Section: Resultsmentioning
confidence: 99%